2011
DOI: 10.1007/s10047-011-0603-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local inflammation of the peritoneal membrane on diuresis and residual renal function in patients treated with peritoneal dialysis

Abstract: The aim of this study was to investigate the connection between local inflammation of the peritoneal membrane and diuresis, as well as the residual renal function (RRF) in patients treated with continuous ambulatory peritoneal dialysis (CAPD). Twenty patients treated with CAPD participated in this cross-sectional study. To determine the influence of local inflammation of the peritoneal membrane, effluent interleukin-6 (IL-6) and soluble interleukin-6 receptor (sIL-6R) levels were measured. The level of IL-6, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The time point chosen in the present study, however, was based on the assumption that 8 wk of PD for a rat corresponds to a patient under long-term PD. Jelicic et al (9) have shown that PD patients have a positive correlation between time on PD and the levels of IL-6 in the peritoneal effluent as well as in plasma, and a higher concentration in effluent compared with plasma, indicating local inflammation that is also reflected systemically. Furthermore, we found that in rats that were exposed to a chronic catheter, but without PD, the hyaluronan and collagen deposition in the interstitial matrix increased to almost the same magnitude as in the dialyzed group.…”
Section: Discussionmentioning
confidence: 97%
“…The time point chosen in the present study, however, was based on the assumption that 8 wk of PD for a rat corresponds to a patient under long-term PD. Jelicic et al (9) have shown that PD patients have a positive correlation between time on PD and the levels of IL-6 in the peritoneal effluent as well as in plasma, and a higher concentration in effluent compared with plasma, indicating local inflammation that is also reflected systemically. Furthermore, we found that in rats that were exposed to a chronic catheter, but without PD, the hyaluronan and collagen deposition in the interstitial matrix increased to almost the same magnitude as in the dialyzed group.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammation plays an important role in the pathogenesis of renal function damage, particularly in the presence of hypertension [20][21][22][23]. It has been suggested that some inflammatory cytokines are significantly related to ineffective erythropoiesis, such as interleukin-1b, IL-6, and tumor necrosis factor-a (TNF-a) that inhibit red blood cell maturation and promote anisocytosis [24,25].…”
Section: Red Blood Cell Distribution and Renal Function Damagementioning
confidence: 99%
“…However, a surprising finding was the lack of correlation between increase of serum IL6 during the whole study and decrease of GFR. Also, Jelicic et al found in peritoneal dialysis patients that the effluent IL6 level correlated with residual diuresis but not with GFR [9]. It seems that the stimulated synthesis of IL6 in endothelial cells observed in our experiments after their exposure to serum samples harvested from the patients could reflect their activation by progressing uremia and treatment with hemodialysis [19].…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Borges et al described the relationship between residual diuresis in patients on hemodialysis and the serum level of CRP [8]. Other authors suggested a link between intraperitoneal IL6 level in patients treated with chronic peritoneal dialysis and their residual renal diuresis [9]. In another study on peritoneal dialysis patients a correlation between serum FGF21 level and residual renal function was described [10].…”
Section: Introductionmentioning
confidence: 90%